A Systematic Review of Knowledge and Perception Regarding Generic Medicines Among Indonesians - Pandanwangi TW, Siti; Agustina, Diana; Karsidin, Bambang (Newinera Publisher, 2024)
Generic medicines are a type of medicine with an official name that has been assigned to the efficacious substance it contains. Generic medicines have the same effectiveness as patented medicines. Many people think that generic medicines are of low quality, so they prefer branded generic medicines or patented medicines. This systematic review aims to report the results of a search for previously reviewed studies that focus on the level of public knowledge and perception of generic medicines. The research method used is a literature study method using journal data from the last 10 years. Journal collection was carried out by searching online journal databases indexed in Google Scholar, and PubMed using Mesh (Medical Subject Headings) with a focus on the keywords